THE EFFECTIVENESS OF USING METAVERSE PLATFORMS AS A COLLABORATIVE LEARNING MEDIA IN HIGHER EDUCATION: A LITERATURE REVIEW - Gilang Ramadhan; Tata Ardiansyah; Yulaeha (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Introduction: Metaverse provides an immersive learning experience that enables virtual collaboration to mimic in-person interactions. Its use in higher education has the potential to increase engagement and learning effectiveness, but in-depth studies are still needed to assess the results and challenges. Objective: To assess the effectiveness of using the metaverse platform as a collaborative learning medium in higher education and to identify supporting and inhibiting factors for its implementation. Method: Researchers collected, analyzed, and synthesized information from various reputable national journals (minimum SINTA 3) and international scientific articles related to the topic of metaverse and collaborative learning. The analysis was conducted using a systematic review approach to understand the pattern of findings and implementation trends in the higher education context. Discussion: The results of the review indicate that metaverse-based learning improves student collaboration, participation, and motivation. Successful implementation is influenced by infrastructure readiness, digital literacy, and interactive activity design. The main obstacles include limited devices, networks, and pedagogical adaptation of lecturers. Recommendations: Technopedagogical training for educators, strengthening of digital infrastructure, and guidelines for metaverse-based learning design that focus on interaction and learning objectives are needed.